Kolaborasi Antar Aktor dalam Pengembanfan Objek Wisata Terbuka Hijau di Syrakarta - Zulaida, Arifah Nurma; Yosafat Hermawan Trinugraha (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2025)
The increasing need for green open spaces RTH in urban areas is in line with the development of cultural and nature based tourist destinations The revitalization of Balekambang Park into a green open tourist attraction in Surakarta City is a real example of collaboration between actors in developing tourist attractions This study aims to analyze how the collaboration process between actors involved in the development of Balekambang Park after revitalization with a case study approach to understand the dynamics of the collaboration that was formed Data collection was carried out through in depth interviews observations and literature studies then analyzed by triangulation by comparing data obtained from various sources of information Analyzed using Talcott Parsons Structural Functionalism theory with the AGIL scheme The selection of informants was carried out by purposive sampling involving UPTD Tourism Areas art studios MSMEs and the Community The results of the study showed that there was collaboration between the government Culture and Tourism Office Ministry of PUPR art studios MSMEs and the community The results of the collaboration are reflected in the adaptation stage namely by socializing and communicating the revitalization project and how to adapt to existing changes the achievement of goals is reflected in efforts to increase tourists and PAD integration is carried out by holding regular coordination forums with related actors and latency is shown by the occurrence of good communication between actors < p>